Performance of School Principal at State Islamic Senior High School in Ex-Surakarta Region - Wahab Wahab (Analisa: Journal of Social Science and Religion, 2012)
This research aims to identify the percentage of the influence of school Organization and motivation atmosphere on Principal’s performance at Madrasah Aliyah (state Islamic  senor  high  school).  This  study  employs  a  co-relational  survey  method. Results of the research show that: (1) average performance of the school principals is good especially on doing their main job and function; (2) the atmosphere of school organization influence significantly on the principal’s performance, the percentage of this influence to Principal performance is 71.30%; (3) work motivation affects significantly to principal performance, the percentage of this influence to principal’s performance is 73.80%; (4) Both school organization atmosphere and work motivation are significantly influential to principal’s performance, the percentage of these to principal’s performance is 78.70%, and (5) work motivation variable is the strongest contribution to influence principal’s performance at 51.60%.